Experimental investigation on flow boiling heat transfer of R1233zd(E) in a variable width parallel microchannel - CAI Huayu; FANG Yidong; LU Di; JIANG Chenhan (Zhileng xuebao)
In this study, the subcooled flow boiling heat transfer of R1233zd(E) in uniform width microchannel and variable width parallel microchannel was experimentally investigated. The flow boiling curves, heat transfer coefficients and pressure drop of the two channel structures under different working conditions were analyzed and compared. The experimental results showed that onset of nucleate boiling (ONB) occured earlier in variable width microchannel than in uniform width parallel microchannel at the same heat flux and can maintain lower wall temperature. In addition, the overall heat transfer characteristic of variable width microchannel is better than that of uniform width microchannel. At high heat flux of qeff=150 kW/m2, the heat transfer coefficient (HTC) of the variable width microchannel is increased by 30%~50% compared with uniform width microchannel, and the maximum value can reach 60%. However, it was worth noting that due to the friction loss caused by the special structure, the two-phase pressure drop of the variable width microchannel was generally greater than that of the uniform width microchannel.